Factors and processes of soil formation of the Karkaraly State National Natural Park - Myrzabaev, A.B.; Amanzholov, A.I.; Golovanov, D.L.; Bodeyev, М.Т.; Urbaniak, J. (Fundamental and Experimental Biology, 2023)
The article presents the results of the work carried out on the analysis of factors and processes of soil for-mation of the Karkaraly State National Natural Park. In the studied area of the soil cover of the national park, it was noted that they develop due to two main factors — vertical zoning and geological specificity of the re-gion. The soils of the area consist of granite, diorite and metamorphic dense rocks. All ancient rocks are cov-ered with quaternary deposits of varying thickness. The work done began with the preparation of routes to control points and a research program. After that, work was carried out on the study of control points: the cre-ation of soil sections — the description of morphological properties of soils, obtaining soil samples along the horizons. The field work was carried out in forest, mountain-forest and steppe landscapes. According to the soil sections of the test points in these places, their color was determined on the Mansell scale. The moisture and granulometric composition of the soil and the boiling of hydrogen chloride were determined.